Enhanced osteoblast adhesion to drug-coated anodized nanotubular titanium surfaces - George E Aninwene II (Dove Medical Press, 2008)
George E Aninwene II1, Chang Yao2, Thomas J Webster21Department of Biochemical Engineering, University of Maryland, Baltimore, MD; 2Division of Engineering, Brown University, Providence, RI, USAAbstract: Current orthopedic implants have functional lifetimes of only 10–15 years due to a variety of reasons including infection, extensive inflammation, and overall poor osseointegration (or a lack of prolonged bonding of the implant to juxtaposed bone). To improve properties of titanium for orthopedic applications, this study anodized and subsequently coated titanium with drugs known to reduce infection (penicillin/streptomycin) and inflammation (dexamethasone) using simple physical adsorption and the deposition of such drugs from simulated body fluid (SBF). Results showed improved drug elution from anodized nanotubular titanium when drugs were coated in the presence of SBF for up to 3 days. For the first time, results also showed that the simple physical adsorption of both penicillin/streptomycin and dexamethasone on anodized nanotubular titanium improved osteoblast numbers after 2 days of culture compared to uncoated unanodized titanium. In addition, results showed that depositing such drugs in SBF on anodized titanium was a more efficient method to promote osteoblast numbers compared to physical adsorption for up to 2 days of culture. In addition, osteoblast numbers increased on anodized titanium coated with drugs in SBF for up to 2 days of culture compared to unanodized titanium. In summary, compared to unanodized titanium, this preliminary study provided unexpected evidence of greater osteoblast numbers on anodized titanium coated with either penicillin/streptomycin or dexamethasone using simple physical adsorption or when coated with SBF; results which suggest the need for further research on anodized titanium orthopedic implants possessing drug-eluting nanotubes.Keywords: anodization, titanium, adhesion, simulated body fluid, nanotubes, osteoblasts